2015
DOI: 10.1038/srep16913
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sources of Infection and Potential Endemic Characteristics of the Large Outbreak of Dengue in Guangdong in 2014

Abstract: A large outbreak of dengue, with the most documented cases, occurred in Guangdong China in 2014. Epidemiological studies and phylogenetic analysis of the isolated dengue virus (DENV) showed this outbreak was attributed to multiple sources and caused by at least two genotypes of DENV-1 (Genotypes I and III) and two genotypes of DENV-2 (Cosmopolitan and Asian I Genotypes). A retrospective review and phylogenetic analysis of DENV isolated in Guangdong showed that DENV-1 Genotype I strains were reported continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 27 publications
(36 reference statements)
1
34
0
Order By: Relevance
“…Dengue outbreaks worldwide have progressively increased [9][10][11][12][13][14], with recent outbreaks in the North Africa and Middle East regions [1,15,16]. In recent years, bibliometric analysis has been widely conducted to evaluate scientific research activities in many fields of infectious diseases such as chikungunya [17], Ebola virus disease [18,19], influenza [20], John Cunningham virus [21], leishmaniasis [22,23], Mayaro virus fever [24], Malaria [25], yellow fever disease [26], and Zika virus [27].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue outbreaks worldwide have progressively increased [9][10][11][12][13][14], with recent outbreaks in the North Africa and Middle East regions [1,15,16]. In recent years, bibliometric analysis has been widely conducted to evaluate scientific research activities in many fields of infectious diseases such as chikungunya [17], Ebola virus disease [18,19], influenza [20], John Cunningham virus [21], leishmaniasis [22,23], Mayaro virus fever [24], Malaria [25], yellow fever disease [26], and Zika virus [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, China experienced a severe dengue outbreak in 201423 in comparison to the outbreak in 2013 with the peak value of case counts exceeding 25,000 in the month of October (see Fig. 3(e)).…”
Section: Resultsmentioning
confidence: 97%
“…Disease-related news articles were provided by HealthMap19, an internationally recognized, global disease alert system capturing outbreak reports from over 200,000 electronic news sources. EpiNews was evaluated on multiple outbreaks in the recent past, such as whooping cough in U.S. (2012)20, periodic outbreaks of avian influenza A(H7N9)2122 and hand, foot, and mouth disease (HFMD) in China (2013 and 2014), periodic outbreaks of acute diarrheal disease (ADD) in India (2013 and 2014), major dengue outbreaks in China (2014)23 and India (2013). Our experiments indicate that EpiNews was successfully able to capture the dynamics of the mentioned outbreaks and estimate the case counts in many of these instances before official reports were published.…”
mentioning
confidence: 99%
“…However, in addition to the frequent importation of viral agents, risk factors such as the expansive distribution of Aedes albopictus Xie et al, 2013), suitable climate conditions for mosquito vector breeding, and uncontrolled urbanization contribute to the expansion of DF epidemics. These factors promote the potential for transformation of an imported epidemic to endemic (Shen et al, 2015;Chen and Han, 2016). In the past, strategies for controlling DF have focused more on coastal regions in Fujian; however, the diversity of the viral source and geographical expansion of DF suggested that it was necessary to strengthen epidemiological and etiological surveillance, not only in coastal regions but also in inland regions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high sequence identity (more than 99.3%) with the virus found in Indonesia (JF967877/ Indonesia/2009), the viral source of the local DF outbreak in 2004 (genotype I) was thought to be countries in Southeast Asia, including Indonesia. DENV1 has continually circulated in Guangdong province for at least 18 years since 1997 (Shen et al, 2015). Phylogenetic analysis revealed that DENV1 caused a large outbreak in Guangdong in 2014 and included genotypes I, IV, and V (Sun et al, 2016).…”
Section: Denv1mentioning
confidence: 99%